Access to Interprofessional Continuing Education in Integrated Care Through Digital Instructional Technology. (17th July 2017) - Lapidos, Adrienne; Ruffolo, Mary
ABSTRACT: In preparing the workforce for integrated care, continuing professional education serves a critical role. Within a rapidly changing health care landscape, matriculated students now benefit from pedagogical innovations supporting integrated care, particularly interprofessional education, and working professionals must not be excluded from this transformation. University-based digital instructional programs can support the learning needs of working professionals, providing an alternative and complement to brick-and-mortar classrooms and ad hoc onsite trainings. This paper describes the structure, content, digital approach, and outcomes of a continuing education program in integrated behavioral health and primary care, housed in a school of social work at a major university. The challenges of interprofessional digital education are described and future directions are suggested.